TEACHING OF RECOUNT TEXT: A Qualitative Study of Second Graders in Junior High School - Esti Puspitasari, - (2011)
The present study, entitled "Teaching of Recount Text"potrays the techniques used by English teachers in one of public junior high school in Bandung. This study is qualitative study, involving two English Teachers of junior high school. Observation, interview, and documents were employed to obtain data needed. The data from observation and document were analyzed to identify the techniques used by teachers, and the data from interview was analyzed to find out students responses towards the techniques. The findings of this study showed that the two teachers used various techniques in teaching recount text. Teacher A used the presentation, question and answer, picture strips story, story telling and warp up. Teacher B used the brainstorming, teacher's silence, question and answer, getting students' to self correction, content explanation, identification and copying. The students have different response to the technqiues used by both teachers. They respond positively to the techniques delivered by teacher A, whereas to the techniques delivered by teacher B is negative.